A pan‐European, multipopulation assessment of migratory connectivity in a near‐threatened migrant bird. Issue 9 (21st July 2015) - Finch, Tom; Saunders, Philip; Avilés, Jesús Miguel; Bermejo, Ana; Catry, Inês; de la Puente, Javier; Emmenegger, Tamara; Mardega, Ieva; Mayet, Patrick; Parejo, Deseada; Račinskis, Edmunds; Rodríguez‐Ruiz, Juan; et al.
Abstract Aim The extent to which individuals from different breeding populations mix throughout the non‐breeding season (i.e. 'migratory connectivity') has important consequences for population dynamics and conservation. Given recent declines of long‐distance migrant birds, multipopulation tracking studies are crucial in order to assess the strength of migratory connectivity and to identify key sites en route. Here, we present the first large‐scale analysis of migration patterns and migratory connectivity in the globally near‐threatened European roller Coracias garrulus. Location Breeding area: Europe; passage area: Mediterranean, sub‐Saharan Africa, Arabian Peninsula; wintering area: southern Africa. Methods We synthesize new geolocator data with existing geolocator, satellite tag and ring recovery data from eight countries across Europe. We describe routes and stopover sites, analyse the spatial pattern of winter sites with respect to breeding origin and quantify the strength of connectivity between breeding and winter sites. Results We demonstrate the importance of the northern savanna zone as a stopover region and reveal the easterly spring loop (via Arabia) and leapfrog migration of rollers from eastern populations. Whilst there was some overlap between individuals from different populations over winter, their distribution was non‐random, with positive correlations between breeding and autumn/winter longitude as well as between pairwise distance matrices of breeding and winter sites. Connectivity was stronger for eastern populations than western ones. Main conclusions The moderate levels of connectivity detected here may increase the resilience of breeding populations to localized habitat loss on the winter quarters. We also highlight the passage regions crucial for the successful conservation of roller populations, including the Sahel/Sudan savanna for all populations, and the Horn of Africa/Arabian Peninsula for north‐eastern rollers.